LEADERSHIP OF VILLAGE KYAI IN THE INFLUENCE OF RELIGIOUS MODERATION - Sarkowi, Sarkowi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research is descriptive qualitative in nature with a phenomenological approach in analyzing the leadership of village Kiai in efforts to mainstream religious moderation for the abangan in Songon, Pondok Joyo, Semboro Jember, East Java. The results of this research show that the leadership authority of village Kiai in the global era has not been shifted, continues to exist, and is the main reference in providing example, da'wah, education and consultation in building the foundation for mainstreaming religious moderation. In implementing his leadership, he uses a situational approach based on religious ethics, through various activities that are routine and conditional, daily, weekly, monthly and yearly, taking into account the context and culture of the Songon community. In leading various religious and non- religious activities, he always instills values, develops attitudes and thoughts that are moderate, tolerant and peaceful as well as love for the Indonesian homeland by referring to the concepts that have been taught or embraced by the NU organization through educational, religious and cultural activities.